Catsper1 promoter is bidirectional and regulates the expression of a novel lncRNA - Jiménez-Badillo, Salma E. (Sci Rep, 2017)
The Catsper1 gene, whose expression is restricted to male germ cells, has great importance in reproductive biology because of its function in sperm motility and fertilization. We previously reported that the promoter of this gene has transcriptional activity in either direction in a heterologous system. In the present study, we found that the Catsper1 promoter has in vitro transcriptional activity in either orientation in GC-1 spg mouse spermatogonial cells. The results also showed that this promoter regulates the expression of a new divergent Catsper1 gene named Catsper1au (Catsper1 antisense upstream transcript). Catsper1au is expressed in adult male mouse testis and liver tissues but not in female mouse liver or ovary tissues. In the testis, Catsper1au is expressed in embryos at 11.5 days post-coitum and from newborns to adults. This gene is also expressed in 1- to 3-week postnatal hearts and in 1-week to adult stage livers. The analysis of the 1402 bp whole genome sequence revealed that Catsper1au is an intronless and polyadenylated lncRNA, located in the nuclei of Sertoli and spermatogenic cells from adult testis. These data indicate that Catsper1au is divergently expressed from the Catsper1 promoter and could regulate gene expression during spermatogenesis.